Beyond the myths and magic of mentoring how to facilitate an effective mentoring process - Murray, Margo 1935- (Jossey-Bass, 2001)
Many managers believe that effective mentoring is most often the lucky result of personal chemistry between two people. But in this book, author Margo Murray lays that myth to rest. Her guide gives you all the expert advice, tools, and case studies you'll need to harness the power of mentoring. Building on the solid principles outlined in the first book, this revised edition adds examples of mentoring from recent publications and the author's client experience. It also includes international examples. It reveals how mentoring can maximize employee productivity and provides information on how t.
Includes bibliographical references (pages 213-218) and index. - Print version record
Keywords: Mentoring in business; Personnel management; Mentorat dans les affaires; Personnel; Direction; BUSINESS & ECONOMICS; Training; BUSINESS & ECONOMICS; Mentoring & Coaching